Faktor-Faktor yang Berhubungan dengan Gangguan Pendengaran pada Pekerja Operator PT. X di Kota Bontang - Tsabita Radhiya Dzakira; Muhammad Sultan; Ida Ayu Indira Dwika Lestari; Iwan Muhamad Ramdan; Dewi Novita Hardianti (Fakultas Kesehatan Masyarakat Universitas Andalas, 2026)
Noise in the workplace is a major risk factor that can cause hearing loss, especially in the oil and gas industry, which has high noise exposure. Long-term exposure to noise above the Threshold Limit Value (TLV) can cause permanent Noise-Induced Hearing Loss (NIHL). Based on observations at PT. X, Bontang City, several areas showed noise levels above 85 dBA, potentially causing hearing impairment among workers. This study aims to determine the relationship between noise levels, length of service, use of hearing protection devices (HPDs), and noisy hobbies or activities with hearing loss among operators at PT. X in Bontang City. The study used a cross-sectional design with a quantitative approach. Data were obtained through noise measurements, questionnaires, and audiometric examination results. Analysis was performed using Spearman's Rank Correlation test to assess the relationship between variables. The results of the study show a significant relationship between noise levels (p=0.000, r=0.951), the use of hearing protection devices (p=0.000, r=- 0.645), and noisy hobbies or activities (p=0.006, r=0.398) with hearing impairment (p<0.05). However, the variable of length of service did not show a significant relationship (p=0.055, r=0.282). It can be concluded that noise levels, the use of hearing protection devices (HPDs), and noisy hobbies or activities are associated with hearing loss, while length of service is not. It is recommended that companies conduct regular audiometric examinations at least twice a year, create Noise Contour Maps on a routine basis, and update noise warning signs in the workplace. The selection of comfortable EPP and education regarding the use of high-risk earphones are also necessary to prevent hearing loss and increase workers' awareness of the dangers of noise.